Dynamics of the soil seed bank over the short-term after bush clearing in a semi-arid shrubland in Springbokvlakte thornveld of South Africa - Mndela, M.; Madakadze, I.C.; Nherera-Chokuda, F.; Dube, Sikhalazo (Elsevier, 2019)
Soil seed bank is a reservoir for passive restoration of rangelands following bush clearance. This study was conducted to assess the effects of bush clearance on the seed bank size, composition, diversity and relationship between soil seed bank (SSB) and above ground vegetation (AGV) in Springbokvlakte thornveld. The study was conducted at Radi communal rangeland, Makapanstad in North-West Province, South Africa with an average rainfall of 459 mm annum−1. The rangeland was encroached at an average density of 6908 woody plants ha−1 by Vachellia tenuispina, Vachellia tortilis, Ziziphus mucronata and Asparagus laricinus, with V. tenuispina accounting for 92% of the woody cover. All woody plants within 50 × 25 m plots were mechanically cut using manual saws and loppers followed by chemical stump treatment using picloram. The cleared and their adjacent uncleared microsites were marked in the middle of a large shrubland and were protected from grazing. Soil samples were collected at three depths (0–10, > 10–20 and > 20–30 cm) in April (pre-treatment), August, October, December 2016 and, April and August 2017 in bush cleared and uncleared microsites. SSB was determined using the seedling emergence method. Vegetation surveys were conducted in February 2016 (pre-treatment) and 2017 (post-treatment). Thirty-seven species from 16 families emerged from the SSB. Perennial species were the most abundant life-form until December 2016, after which annuals increased to 70 and 71% in April and August 2017, respectively in cleared microsites. Eragrostis lehmanniana, Jamesbrittenia aurantiaca and Aristida bipartita were the most abundant species until December 2016, thereafter; Brachiaria eruciformis dominated by 55–61% from April to August 2017 in cleared microsites. Principal component analysis (PCA) revealed that most seed bank species correlated strongly with total soil nitrogen, C:N ratio and nitrates. Total seed densities remained similar from August to December 2016, thereafter; they were 2- to 3-fold higher in cleared compared to uncleared microsites. Seed densities declined significantly (p < .05) with burial depth in April and August 2017 in cleared microsites. Species diversity declined with time in cleared relative to uncleared microsites, mainly due to B. eruciformis homogenising the SSB in April and August 2017, respectively. In contrast, SØrensen's similarity between SSB and AGV increased with time, being highest in cleared than uncleared microsites from December 2016 to August 2017. Large seed bank densities in cleared microsites indicated high potential for vegetation recovery following bush clearance. However, follow-up management to drive vegetation changes to perennial species dominated state is necessary.